Primary cutaneous anaplastic large cell lymphoma T/ALK– in a child with atypical presentation. - Benhayoun, F.; Hali, F.; Marnissi, F.; Chiheb, S. (European Journal of Pediatric Dermatology, 2023)
Anaplastic large cell lymphoma (ALCL) is a CD30+ T-cell non-Hodgkin’s lymphoma. It includes two distinct entities: a primary cutaneous (PC-ALCL), which has no systemic involvement, and a systemic ALCL. PC-ALCL is very rare in children compared to the systemic form. Here was reported a rare case of PC-ALCL with atypical presentation in a child.